Sports Industry Management Survey in Demak Regency - Amad Fa'is; Tri Nurharsono; Lulu April Farida; Agus Widodo Suripto (Universitas Majalengka, 2021)
The purpose of the research to know the description of management includes planning, organizing, driving, and supervision of sports industry management in Demak District. Methods This research is a survey research using qualitative descriptive approach. The result of this research is 1) The planning process done by sports industry in Demak Regency has been run in accordance with the management function, 2) The management of sports industry in Demak Regency is still lacking, because the whole of sports industry does not have organizational structure so there are many double function to the owner and employees, 3) The management of sports industry in Demak Regency is quite good, because the communication between owner, manager and employee is good, employees also execute manager's orders well in accordance with their duties, 4) Sports industry supervision management in Demak Regency is good, because all owners always supervise their employees.